Facile one-pot synthesis of porphyrin based porous polymer networks (PPNs) as biomimetic catalysts1. Issue 19 (7th March 2015) - Zou, Lanfang; Feng, Dawei; Liu, Tian-Fu; Chen, Ying-Pin; Fordham, Stephen; Yuan, Shuai; Tian, Jian; Zhou, Hong-Cai
<x xml:space="preserve">Abstract</x> Two stable porphyrin based porous polymer networks (PPNs) were synthesized, and their biomimetic catalytic activities were studied.